2007
DOI: 10.1103/physrevlett.98.084502
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Particle Concentration in Turbulence at Dissipative and Inertial Scales

Abstract: Document VersionPublisher's PDF, also known as Version of Record (includes final page, issue and volume numbers) Please check the document version of this publication:• A submitted manuscript is the author's version of the article upon submission and before peer-review. There can be important differences between the submitted version and the official published version of record. People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

40
339
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 328 publications
(382 citation statements)
references
References 21 publications
40
339
3
Order By: Relevance
“…Previous studies have demonstrated that the trajectories of passive tracer particles integrated via this numerical scheme accurately capture both the velocity 46 and the acceleration 47 statistics of the underlying DNS-derived flow. Moreover, previous studies on clustering of inertial particles 48 have demonstrated the efficacy of this method to resolve sub-Kolmogorov scale fractal aggregations, which we also observed for gyrotactic swimmers.…”
Section: ã2supporting
confidence: 52%
“…Previous studies have demonstrated that the trajectories of passive tracer particles integrated via this numerical scheme accurately capture both the velocity 46 and the acceleration 47 statistics of the underlying DNS-derived flow. Moreover, previous studies on clustering of inertial particles 48 have demonstrated the efficacy of this method to resolve sub-Kolmogorov scale fractal aggregations, which we also observed for gyrotactic swimmers.…”
Section: ã2supporting
confidence: 52%
“…Numerical studies [10,50] show that the qualitative St-dependence of D 2 is similar to that observed in the Kraichnan model. Despite such similarities, it is likely that in turbulence, ejection from vortical regions play, at least for small St, an important role [50]. This can clearly not be accounted for in Kraichnan flows, as δ-correlated flows have no persistent structures.…”
Section: Remarks and Conclusionmentioning
confidence: 62%
“…However, while in the Kraichnan case the particle distribution depends on the local Stokes number St(r) only, this does not seem to be the case in turbulence, at least for St(r) ≪ 1 as studied in [50] ( which in turbulence is defined by St(r) = τ /τ r , τ r being the characteristic turbulent time scale associated to the scale r). In turbulent flows, for small values of St(r), a different rescaling related to that of the acceleration (and hence pressure) field has been found [50]. However such discrepancies do not question the relevance of the Kraichnan model to turbulent flows as it is expected to be a good approximation only for scales r such that τ r ≪ τ , i.e.…”
Section: Remarks and Conclusionmentioning
confidence: 99%
“…For values of St not too large, the RDF for a monodisperse system typically takes the form of a power law which reflects the multi-scale self-similar nature of droplet clustering (e.g. Figures 7 and 8 of Goto and Vassilicos, 2006;Bec, 2005;Bec et al, 2007). This multi-scale clustering has been accounted for in terms of the sweep-stick mechanism, which explains why droplet clustering mimics the multi-scale clustering of vanishing fluid acceleration points in a turbulent flow (Coleman and Vassilicos, 2009).…”
Section: Droplet Clusteringmentioning
confidence: 99%